Environmental risks and opportunities for countries along the Belt and Road: Location choice of China's investment. (20th February 2019) - Huang, Yanying
Abstract: Chinese investment in the "Belt and Road Initiative" (BRI) will have an impact on a host country's environment. At the same time, the resource endowments and environmental capacity of a host country will also affect international investment. Geographic Information System (GIS) maps and a risk-opportunity matrix generated to assess environmental risks and to explore opportunities within 64 countries along the "Belt and Road" (B&R) have been dialectically applied to determine investment locations. This paper aims to help Chinese enterprises choose suitable investment locations with respect to balancing the investment, environment, and resource potential of host countries. The findings indicate that Singapore, Bhutan, Nepal, Myanmar, Laos, and most countries in Central and Eastern Europe have the best environmental conditions for investment. Conversely, India has the least ideal environmental conditions. Based on these results, the BRI could be designed and implemented more intelligently to maximize return while minimizing ecological harm to the environment.